2012
DOI: 10.1007/s00586-012-2635-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of surgery on neurological outcome and survival in metastatic spinal cord compression

Abstract: Purpose Metastatic spinal cord compression (MSCC) requires expeditious treatment. While there is no ambiguity in the literature about the urgency of care for patients with MSCC, the effect of timing of surgical intervention has not been investigated in detail. The objective of our study was to investigate whether or not the 'timing of surgery' is an important factor in survival and neurological outcome in patients with MSCC. Methods All patients with MSCC presenting to our unit from October 2005 to March 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 18 publications
8
62
2
2
Order By: Relevance
“…No study reported a significant effect of time-to-surgery following the onset of spinal cord compression symptoms on survival. 36 Quraishi et al 36 reported that there was no significant difference between 3 groups treated with surgery within 24 hours, between 24 and 48 hours, and over 48 hours from acute presentation of neurological symptoms with respect to survival (p = 0.99). Finally, in a randomized, multiinstitutional, nonblinded trial, Patchell et al 32 found that surgical treatment followed by radiotherapy compared with radiotherapy alone resulted in increased median survival time (126 days vs 100 days, respectively; RR 0.6, p = 0.03).…”
Section: Predictors Of Survivalmentioning
confidence: 99%
“…No study reported a significant effect of time-to-surgery following the onset of spinal cord compression symptoms on survival. 36 Quraishi et al 36 reported that there was no significant difference between 3 groups treated with surgery within 24 hours, between 24 and 48 hours, and over 48 hours from acute presentation of neurological symptoms with respect to survival (p = 0.99). Finally, in a randomized, multiinstitutional, nonblinded trial, Patchell et al 32 found that surgical treatment followed by radiotherapy compared with radiotherapy alone resulted in increased median survival time (126 days vs 100 days, respectively; RR 0.6, p = 0.03).…”
Section: Predictors Of Survivalmentioning
confidence: 99%
“…Another paper dealing with surgical treatment of spinal metastasis was that of Quraishi et al [44]. They retrospectively reviewed 121 patients admitted and operated upon in their unit, 45 within 24 h, 23 between 24 and 48 h, and 53 after 48 h. Although the time of surgery did not influence time of hospital stay, incidence of infection postoperative complications or survival, it did influence the degree of neurological recovery.…”
Section: Tumoursmentioning
confidence: 99%
“…Favorable functional outcome is associated with duration of paralysis less than 48 hours [4], pretreatment ambulation, good performance status [5,6], surgery [2,7], high Tokuhashi score [8], high Japanese Orthopaedic Association score [9], and absence of visceral metastases [10]. Perhaps, the duration of paralysis, the pretreatment ambulatory status, and therapeutic methods were the most important factors for functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical characteristics related to postoperative functional outcome have been proposed: the duration of paralysis [4], pretreatment ambulatory status, preoperative performance status [5,6], therapeutic methods (surgery or radiotherapy) [2,7], Tokuhashi score [8], Japanese Orthopaedic Association score [9], and visceral metastases [10]. Moreover, Rades et al [11] developed a scoring system for predicting postradiotherapy ambulatory outcome, which comprised five prognostic factors, including primary tumor type, interval between tumor diagnosis and MESCC, visceral metastases, motor function, and time until motor deficits developed, in a series of 2,096 patients.…”
Section: Introductionmentioning
confidence: 99%